2022
DOI: 10.1155/2022/2803540
|View full text |Cite
|
Sign up to set email alerts
|

Association between Stigma and Pain in Patients with Temporomandibular Disorders

Abstract: Objective. This study aims to explore the association between stigma and pain in patients with temporomandibular disorders (TMDs). Methods. Two hundred and twenty-five patients with TMDs were recruited, and they completed the questionnaires including the Visual Analogue Scale of Pain (VAS), Generalized Anxiety Disorder 7-Item (GAD-7), the Patient Health Questionnaire 9-item (PHQ-9), Jaw Functional Limitation Scale 8-item (JFLS-8), the Stigma Scale for Chronic Illness 8-item (SSCI-8), and other demographic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Adjustment for several confounding factors was conducted in this study, but residual confounding effects still remains possible. Multiple psychological factors such as stress and stigma are suggested associated with patients' sleep status and TMD symptoms 34–36 . Some studies indicated that various lifestyle habits, health condition, and mental states such as psychotropic medication use, caffeine intake, use of electronic devices, cognitive factors, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adjustment for several confounding factors was conducted in this study, but residual confounding effects still remains possible. Multiple psychological factors such as stress and stigma are suggested associated with patients' sleep status and TMD symptoms 34–36 . Some studies indicated that various lifestyle habits, health condition, and mental states such as psychotropic medication use, caffeine intake, use of electronic devices, cognitive factors, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple psychological factors such as stress and stigma are suggested associated with patients' sleep status and TMD symptoms. [34][35][36] Some studies indicated that various lifestyle habits, health condition, and mental states such as psychotropic medication use, caffeine intake, use of electronic devices, cognitive factors, etc. might act as mediating factors or confounding factors in the relationship between sleep disorders and the development of TMD.…”
Section: Ta B L Ementioning
confidence: 99%
“…2,3 The main clinical symptoms include orofacial pain, joint noise and impaired jaw function. 4,5 The aetiology of TMD has long been controversial. 6,7 In recent years, the biopsychosocial medicine perspective has gradually gained widespread recognition, and the onset and development of TMD are considered to be the result of a combination of genetic, environmental, psychological and social factors, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies indicate that TMD affects about 5%–12% of the total population, with an annual incidence of 3.9% 2,3 . The main clinical symptoms include orofacial pain, joint noise and impaired jaw function 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] The influence of various symptoms of TMD has been widely investigated and proven to be associated with psychological disorders, systemic disorders and overlapping pain conditions. 7,8,[11][12][13][14][15] As one of the most common symptoms of TMD, pain in the maxillofacial region, especially chronic pain persisting for a long time, was associated with negative emotions of the patients such as depression, stress, anxiety, and stigma as well as increased pain sensitivity. 7,14,15 The increased pain sensitivity caused by TMD has been related to the genetic factors and psychological disorders mentioned above and may be the result of an abnormal response of the central nervous system to nociceptive information induced by physical or emotional stress.…”
Section: Introductionmentioning
confidence: 99%